2010
DOI: 10.1182/blood-2009-12-256222
|View full text |Cite
|
Sign up to set email alerts
|

Integrin and CD3/TCR activation are regulated by the scaffold protein AKAP450

Abstract: IntroductionDuring the process of antigen recognition by T cells, structural and spatial changes take place at the immune synapse (IS) formed at the contact with antigen-presenting cells (APCs), involving various recognition and signaling molecules as well as cytoskeletal components. In T cells, the IS contains a central supramolecular activation cluster (c-SMAC), which includes the T-cell receptor (TCR)/CD3 complex and various costimulatory receptors, and a peripheral ring (p-SMAC) where molecules, such as ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 50 publications
2
47
1
Order By: Relevance
“…3C) following 12% strain resulted in proteins that are associated with both normal and diseased cellular processes. Normal functioning proteins include kinesin family 14 (KIF14) (95) and kinase anchor proteins (AKAPs), both of which are important in microtubule organization (96). However AKAPs are also associated with cancer (97)(98)(99) and is an important anaphase promoting complex (100).…”
Section: Figmentioning
confidence: 99%
“…3C) following 12% strain resulted in proteins that are associated with both normal and diseased cellular processes. Normal functioning proteins include kinesin family 14 (KIF14) (95) and kinase anchor proteins (AKAPs), both of which are important in microtubule organization (96). However AKAPs are also associated with cancer (97)(98)(99) and is an important anaphase promoting complex (100).…”
Section: Figmentioning
confidence: 99%
“…14 In vivo, a recent study found that an Akap9 null mutant (Akap9 mei2.5/mei2.5 , with a stop codon after exon 14) generated by random chemical mutagenesis and Akap9-deficient male mice with a deletion of exon 8 were infertile. Physiologic and morphologic analysis, performed only for the Akap9 mei2.5/mei2.5 animals, attributed the infertility to a defect in Sertoli cell maturation.…”
mentioning
confidence: 99%
“…Our data indicate that the dynamic association of EWI-2 with a-actinin plays different roles in the formation and maintenance of immune and viral synapses. (43). Then, isolated T lymphoblasts were maintained with recombinant human IL-2 (50 U/ml) for 5 d.…”
mentioning
confidence: 99%